مقومات البحث العلمي الواجب توافرها لخلق قيمة مضافة للجامعات السورية (دراسة ميدانية في جامعة تشرين) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
This study aimed to determine the reality of scientific research in Syria compared to Arab Countries, and some developed countries, by comparing the proportion of expenditure on research and development of local output, the number of researchers and technicians working in research and development, the number of research articles published in international journals, the number of Syrian researchers registered in the Google Scholar search engine, the number of citations to their researches, the number of researches published in Tishreen University, in addition to the number of researches registered and completed for postgraduate students at Tishreen University during the period 2008-2018, the number of Syrian researchers registered in the Researchgate research site, as well as the number of applications for patents for accreditation in the Arab Countries, the value of exports of high technology and the proportion of those exports of transformative exports; and determine the components of scientific research to be available to create added value to the Syrian Universities. The researcher adopted the survey methodology and distributed the questionnaire to 289 members of the teaching staff at Tishreen University. The most important result of the study was that, the participation of the Syrian Universities in attracting talent, participation in local, Arab and international conferences, seminars and workshops, providing research labs, modern computers, participation in search engines, research sites, databases and financing of external publications are effective Foundations for creating added value. Then, some recommendations were presented that would contribute to the creation of added value, the most important of which are: increasing the percentage of expenditure on scientific research, employing researchers, encouraging researchers to publish in international journals, establishing cooperation relations with local, Arab and  international research organizations and developing them. هدفت هذه الدّراسة لتحديد واقع البحث العلمي في سورية مقارنة بالدول العربية وبعض الدول المتقدمة، من خلال مقارنة نسبة الإنفاق على البحث والتطوير من الناتج المحلي، وعدد الباحثين والتقنيين العاملين في البحث والتطوير، وعدد المقالات البحثية المنشورة في دوريات عالمية، وعدد الباحثين السوريين المسجلين في محرك البحث Google Scholar وعدد الاقتباسات لأبحاثهم، وعدد الأبحاث المنشورة في مجلة جامعة تشرين، وأيضاً عدد الأبحاث المسجلة والمنجزة لطلاب الدراسات العليا في جامعة تشرين خلال الفترة 2008-2018، وعدد الباحثين السوريين المسجلين في موقع البحث العلمي Researchgate، وكذلك عدد طلبات الحصول على براءات الاختراع للاعتماد في الدول العربية، وقيمة الصادرات من التكنولوجيا العالية ونسبة تلك الصادرات من الصادرات التحويلية؛ وتحديد مقومات البحث العلمي الواجب توافرها لخلق قيمة مضافة في الجامعات السورية. واعتمد الباحث على منهج المسح، وقام بتوزيع الاستبيان على 289 عضواً من أعضاء الهيئة التدريسية في جامعة تشرين، وكانت النتيجة الرئيسة الأهمّ في الدّراسة هي إنّ قيام الجامعات السورية بجذب الكفاءات، والمشاركة بالمؤتمرات والندوات وورش العمل المحلية والعربية والعالمية، وتوفير المختبرات البحثية والحواسيب الحديثة والاشتراك في محركات البحث والمواقع البحثية وقواعد البيانات وتمويل النشر الخارجي، هي مقومات فعالة لخلق القيمة المضافة، ثم تمّ عرض بعض التوصيات التي من شأنها الاسهام في خلق القيمة المضافة ومن أهمها: زيادة نسبة الإنفاق على البحث العلمي، توظيف باحثين، تشجيع الباحثين على النشر في دوريات عالمية، وتأسيس علاقات التعاون مع المنظمات البحثية المحلية والعربية والعالمية وتطويرها.